The balance between fitness advantages and costs drives adaptation of bacteriophage Qβ to changes in host density at different temperatures - Laguna-Castro, Mara; Rodríguez-Moreno, Alicia; Llorente, Elena; Lázaro, Ester (Frontiers in Microbiology, 2023)
Host density is one of the main factors affecting the infective capacity of viruses. When host density is low, it is more difficult for the virus to find a susceptible cell, which increases its probability of being damaged by the physicochemical agents of the environment. Nevertheless, viruses can adapt to variations in host density through different strategies that depend on the particular characteristics of the life cycle of each virus. In a previous work, using the bacteriophage Qβ as an experimental model, we found that when bacterial density was lower than optimal the virus increased its capacity to penetrate into the bacteria through a mutation in the minority capsid protein (A1) that is not described to interact with the cell receptor. Here we show that the adaptive pathway followed by Qβ in the face of similar variations in host density depends on environmental temperature. When the value for this parameter is lower than optimal (30 ºC), the mutation selected is the same as at the optimal temperature (37 ºC). However, when temperature increases to 43 ºC, the mutation selected is located in a different protein (A2), which is involved both in the interaction with the cell receptor and in the process of viral progeny release. The new mutation increases the entry of the phage into the bacteria at the three temperatures assayed. However, it also considerably increases the latent period at 30 ºC and 37 ºC, which is probably the reason why it is not selected at these temperatures. The conclusion is that the adaptive strategies followed by bacteriophage Qβ, and probably other viruses, in the face of variations in host density depend not only on their advantages at this selective pressure, but also on the fitness costs that particular mutations may present in function of the rest of environmental parameters that influence viral replication and stability.